Pius Vates - Borkowski, Andrzej (Tematy i Konteksty, 2021)
The question dealt with in the paper is as follows: to what extent might the notion of “religious literature” be functional if applied both to the early modern literature and the contemporary literary culture? Does it mean “sacred literature,” simply opposed to the “secular” one, whatever it might mean? The author’s suggestion is to use the notion of “religious literature” more consistently, depending strictly on the liturgical functions of the text (e.g. of prayers, hymns or homilies), while the term “sacred literature” should be used only with reference to the so-called “Sacred Books,” i.e. the Revelation recognized in a given religious system. The sense of the terms “pious literature” or “pious poet,” however, should be much broader, going beyond the limitations of religious functions of the text and reflecting a quasi-prophetic intellectual and moral status of the writer.